COLLABORATIVE GOVERNANCE DALAM PENANGGULANGANKEMISKINAN EKSTREM (PKE) DI KABUPATEN SUMEDANG - Erlanda, Agussyahrul Noer (JRPA - Journal of Regional Public Administration, 2025)
The eradication of extreme poverty is a national development prioritythat requires cross-sectoral and collaborative approaches. This studyaims to analyze the implementation of Collaborative Governance inaddressing extreme poverty in Sumedang Regency, using thetheoretical model proposed by Ansell and Gash (2007), whichincludes four key dimensions: starting conditions, facilitativeleadership, institutional design, and the collaborative process. Aqualitative descriptive method was employed, with data collectedthrough interviews, observations, and documentation. The resultsindicate that collaboration has been implemented through cross-sectoral forums and regional programs such as “One GovernmentAgency, One Assisted Village.” However, several obstacles remain,including cultural, institutional, and political factors such as lack oftrust among actors, underdeveloped technical regulations, andlimited involvement of non-governmental sectors. Efforts to overcomethese challenges include building trust, drafting collaborativestandard operating procedures (SOPs), cross-sectoral training, andinclusive political leadership. The study concludes that CollaborativeGovernance in Sumedang Regency has shown significant progressbut still requires strengthened regulatory frameworks and broadermulti-sector participation to ensure greater effectiveness andsustainability.